2020
DOI: 10.1021/jacs.0c08823
|View full text |Cite
|
Sign up to set email alerts
|

General Method for Enantioselective Three-Component Carboarylation of Alkenes Enabled by Visible-Light Dual Photoredox/Nickel Catalysis

Abstract: A visible-light-promoted photoredox/nickel protocol for the enantioselective three-component carboarylation of alkenes with tertiary and secondary alkyltrifluoroborates and aryl bromides is described. This redox-neutral protocol allows for facile and divergent access to a wide array of enantioenriched β-alkyl-α-arylated carbonyls, phosphonates, and sulfones in high yields and excellent enantioselectivities from readily available starting materials. We also report a modular and enantioselective synthesis of flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(75 citation statements)
references
References 86 publications
3
72
0
Order By: Relevance
“…Prior computational studies of related coupling reactions have suggested that either reductive elimination from Ni(III) or radical addition to tetrahedral Ni(II) is the enantiodetermining step. 27,28 In terms of substrate and ligand identity, this present work is more analogous to the system studied by Gutierrez, Kozlowski, and Molander where reductive elimination is enantiodetermining. In this case, a more electron-donating ligand would be expected to better stabilize Ni(III) leading to a less exergonic step (Figure 3C).…”
Section: Phmentioning
confidence: 98%
“…Prior computational studies of related coupling reactions have suggested that either reductive elimination from Ni(III) or radical addition to tetrahedral Ni(II) is the enantiodetermining step. 27,28 In terms of substrate and ligand identity, this present work is more analogous to the system studied by Gutierrez, Kozlowski, and Molander where reductive elimination is enantiodetermining. In this case, a more electron-donating ligand would be expected to better stabilize Ni(III) leading to a less exergonic step (Figure 3C).…”
Section: Phmentioning
confidence: 98%
“…162,163 Remarkably, Nevado and co-workers 164 further extended this chemistry by using vinyl amides, vinyl boranes, and vinyl phosphates as suitable alkenes (Scheme 18c). Based on previous developments, Chu and co-workers 165 described an interesting visible light-promoted nickel/photoredox dual strategy for the construction of enantioenriched βalkyl-α-arylated carbonyls, phosphonates, and sulfones by employing a series of different olefins (Scheme 18d). Most recently, Chen and co-workers 166 designed a new chiral 8-quinoline imidazoline ligand for the reductive cyclization of monosubstituted alkenes.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In these reactions, substrates such as compounds with an -C(sp 3 )-H adjacent to heteroatom or simple alkanes have been employed to cause a facile HAT process and thus control the regioselectivity. There is still, however, a great demand for the development of a practical protocol using a readily available chemical as an alkyl radical source, [25][26][27] with the aim to construct complex ketones without redundant protection and deprotection process. The carboxylic acids could realize a synthetase-catalyzed formal decarboxylative acylation by transfer of an acyl group from coenzyme A (CoA) activated thioesters to deliver a chain-extended ketone 28 (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%